2019
DOI: 10.3758/s13428-019-01304-3
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive algorithm for fast and reliable online saccade detection

Abstract: To investigate visual perception around the time of eye movements, vision scientists manipulate stimuli contingent upon the onset of a saccade. For these experimental paradigms, timing is especially crucial, because saccade offset imposes a deadline on the display change. Although efficient online saccade detection can greatly improve timing, most algorithms rely on spatialboundary techniques or absolute-velocity thresholds, which both suffer from weaknesses: late detections and false alarms, respectively. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Indeed, showed that contrast sensitivity to a grating drifting at only 100 dva/s decreased by almost one log unit when its spatial frequency was increased from 0.1 to 0.7 cpd, and that gratings drifting at 800 dva/s could only be detected if their SF was below 0.1 cpd. Moreover, Schweitzer and Rolfs (2019) found that Gabor patches (0.5 cpd and 0.5 dva SD Gaussian aperture) rapidly drifting within their aperture (thus not producing any motion streaks) became impossible to detect during fixation when drift velocities came close to or exceeded saccadic peak velocities (∼400 dva/s). Finally, Castet et al (2002) presented striking evidence that intra-saccadic gratings (with orthogonal orientation to the saccade direction, saccadic peak velocities around 280 dva/s) induced motion percepts if their SFs were 0.04 and 0.18 cpd, but not if their SF was 1.81 cpd, because the latter induced temporal frequencies of ∼500 Hz, which cannot be resolved by motion detectors.…”
Section: Visual Processing Of Intra-saccadic Motion Smearmentioning
confidence: 98%
See 3 more Smart Citations
“…Indeed, showed that contrast sensitivity to a grating drifting at only 100 dva/s decreased by almost one log unit when its spatial frequency was increased from 0.1 to 0.7 cpd, and that gratings drifting at 800 dva/s could only be detected if their SF was below 0.1 cpd. Moreover, Schweitzer and Rolfs (2019) found that Gabor patches (0.5 cpd and 0.5 dva SD Gaussian aperture) rapidly drifting within their aperture (thus not producing any motion streaks) became impossible to detect during fixation when drift velocities came close to or exceeded saccadic peak velocities (∼400 dva/s). Finally, Castet et al (2002) presented striking evidence that intra-saccadic gratings (with orthogonal orientation to the saccade direction, saccadic peak velocities around 280 dva/s) induced motion percepts if their SFs were 0.04 and 0.18 cpd, but not if their SF was 1.81 cpd, because the latter induced temporal frequencies of ∼500 Hz, which cannot be resolved by motion detectors.…”
Section: Visual Processing Of Intra-saccadic Motion Smearmentioning
confidence: 98%
“…A horizontal rightward saccade was only detected when its direction was in the range of 360°± 25°, whereas a leftward saccade had to be in the range of 180°± 25°. A more thorough description of the algorithm can be found in Schweitzer and Rolfs (2019).…”
Section: Online Saccade Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…After successful fixation, an exogenous cue was presented to indicate the saccade target: The target stimulus -one of the six presented stimuli and one of the two types of noise patches -was enlarged linearly up to twice its initial size for 25 ms and then decreased for 25 ms until the initial size was restored. Saccades were detected online using the algorithm described by Schweitzer & Rolfs (2019) with parameters k=2, λ=10, and θ=40, on both eyes. As soon as the saccade was detected, the cued stimulus moved 30 deg in a clockwise (CW) or counterclockwise (CCW) direction for 14.6 msamounting to a distance traveled of 5.2 dva at a velocity of approximately 360 dva/s -or remained in its pre-saccadic location.…”
Section: Procedures and Taskmentioning
confidence: 99%